2019
DOI: 10.1140/epjd/e2019-100328-2
|View full text |Cite
|
Sign up to set email alerts
|

Control of electromagnetically induced transparency and Fano resonances in a hybrid optomechanical system

Abstract: We study the control of electromagnetically induced transparency and Fano resonances in a hybrid optomechanical system based on Bose-Einstein condensate trapped inside a high finesse Fabry Pérot cavity coupled with two charged nanomechanical resonators. The system is driven by a pump field and probed by a probe field. The nanomechanical resonators are connected to an external bias voltage V1(−V2) and generated electrostatic Coulomb coupling gc. In this study, we show that the electromagnetically induced transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Besides, it has been shown that hybrid optomechanical systems consisting of atomic systems or BEC may provide more controllability in fast and slow light realization 41 – 47 . Furthermore, the phenomenon of Fano resonance which was observed for the first time in some of the Rydberg spectral atomic lines, can be also observed in optomechanical systems 48 50 .…”
Section: Introductionmentioning
confidence: 77%
“…Besides, it has been shown that hybrid optomechanical systems consisting of atomic systems or BEC may provide more controllability in fast and slow light realization 41 – 47 . Furthermore, the phenomenon of Fano resonance which was observed for the first time in some of the Rydberg spectral atomic lines, can be also observed in optomechanical systems 48 50 .…”
Section: Introductionmentioning
confidence: 77%
“…The physical origin of Fano resonance in the systems having optomechanical-like interactions has explained due to the presence of non-resonant interactions. For example, in a standard optomechanical system, if the anti-Stokes process is not resonant with the cavity frequency, asymmetric Fano shapes appear in the spectrum [30][31][32]. In our system, this corresponds to ∆ m1 = ω b , because instead of a cavity mode, magnon mode m 1 is coupled with phonon mode via optomechanical-like interaction.…”
Section: Fano Resonances In the Output Fieldmentioning
confidence: 88%
“…4(a). Such asymmetric MIT bands can be related to multiple Fano resonances, emerging frequently in optomechanical systems [30][31][32][33][34]. If we remove the YIG1 and consider the other two couplings g 2 and g mb in the system for ∆ m2 = 0.7ω m , we obtain double Fano resonance in the output spectrum, this is shown in Fig.…”
Section: Fano Resonances In the Output Fieldmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, optomechanical system (OMS) has been widely researched and reviewed [1–7], which examines the coupling between the photons and phonons based on the radiation pressure interactions. OMS as a macroscopic system is a good plateform to study the interaction among the nanocavity, the mechanical oscillator and other inserted objects such as atoms [8–15], Bose–Einstein condensate (BEC) [16–21], quibit [22–26], Kerr medium [27–30], graphene [31], QD [27, 32]. Many interesting phenomena have been reported, like optical solitons [33], electromagnetically induced absorption [17, 24, 34], optomechanically induced transparency (OMIT) [12, 13, 24, 26, 31–43], optomechanically induced amplification [24, 45], optical bistability [16, 46, 47], sideband effect [48, 49], entanglement [8, 50], four‐wave mixing [10, 51], squeezing [25, 52, 53], ground‐state cooling [54–59], photothermally induced transparency [60], optomechanically induced birefringence and optomechanically induced faraday effect [61].…”
Section: Introductionmentioning
confidence: 99%